Durablilty propeties of geopolymer concrete partial replacement of fine aggaregate with waste crushed glass. (2022) - Mahesh, Y.; Lalitha, G.
Abstract: This research work focused on durability aspects of geopolymer concrete partial replacement of fine aggregate with waste crushed glass. The waste crushed glass contains a high amount of amorphous silica. The GPC40 grade geopolymer concrete prepared was fly ash, alccofine with constant percentages (85%+15%), alkaline activators, and waste crushed glass. In this research geopolymer concrete GPC40 fine aggregate replaced by waste crushed glass with different percentages 0%, 10%, 20%, 30% & 40% by weight of sand. The alkaline solutions were taken with 10 M. The samples were cured at ambient temperature for 7, 28 and 90 days. The durability tests were conducted after 90 days of ambient curing. Durability tests conducted were acid attack test and half-cell potential test. Sulfuric acid and Hydrochloric acid were taken 5% concertation. Results were compared with normal GPC and waste crushed glass GPC showing better performance in acid attack tests and half-cell potential test. With 40% replacement of waste crushed glass GPC specimens immersed in sulfuric acid the percentage weight loss and strength loss were 2.03 % and 1.81% respectively. With 40% replacement of waste crushed glass GPC specimens immersed in sulfuric acid the percentage weight loss and strength loss were 3.09% and 1.68 % respectively. Half-cell potential results showing increasing glass content decreasing corrosion of steel.